Removal of saponin from palauan (Cyrtosperma merkusii (Hassk.) Schott) corms by solvent extraction - Joaquin, John Albert D.
Palauan (Cyrtosperma merkusii) is a minor crop in the Philippines with limited commercial use because of its inherent soapy taste that maybe associated to its saponin content.